Current predictive controller for high frequency resonant inverter in induction heating - Azzedine Khati; Abdelkader Kansab; Rachid Taleb; Houari Khouidmi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In the context of this article, we are particularly interested in the modeling and control of an induction heating system powered by high frequency resonance inverter. The proposed control scheme comprises a current loop and a PLL circuit. This latter is an electronic assembly for slaving the instantaneous phase of output on the instantaneous input phase, and is used to follow the rapid variations of the frequency.To further improve the transient dynamics of the studied system and in order to reduce the impact of measurement noise on the control signal, a generalized predictive control has been proposed to control the current of the inductor. We discussed the main steps of this command, whose it uses a minimization algorithm to obtain an optimal control signals, its advantages are: its design is simple, less complexity and direct manipulation of the control signal.The results have shown the effectiveness of the proposed method, especially in the parameters variation and/or the change of the reference current.